Parental Presence During Induction: The Role Parents Play Is It Valid? - McGann, Josephine (Operating Room Nurses Association of Canada Journal, 1999)
Pediatric patients preparing for surgery are exposed to a totally unfamiliar environment. The hospital is a very busy, noisy place. People are continuously com- ing and going, dressed in unconventional clothing, wearing funny hats and even covering their faces with masks. This creates anxiety and stress for both the pediatric patient and his/her parents. The perioperative nurse has ten to fifteen minutes to assess her patient to determine their stage of development, their emotional and psychological state, their physical needs and lastly their level of anxiety.